2007
DOI: 10.1021/bi0621821
|View full text |Cite
|
Sign up to set email alerts
|

Vinyldeoxyadenosine in a Sarcin−Ricin RNA Loop and Its Binding to Ricin Toxin A-Chain

Abstract: Abstract8-Vinyl-2'-deoxyadenosine (8vdA) is a fluorophore with a quantum yield comparable to 2-aminopurine nucleoside. 8vdA was incorporated into a 10-mer stem-tetraloop RNA (8vdA-10) structure to characterize the properties of the base, 8-vinyladenine (8-vA), with respect to adenine as a substrate or inhibitor for ribosome inactivating proteins. Ricin Toxin A-chain (RTA) and Pokeweed Antiviral Protein (PAP) catalyze the release of adenine from a specific adenosine on a stem-tetraloop (GAGA) sequence at the el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
(72 reference statements)
0
4
0
Order By: Relevance
“…Inhibitors were designed and synthesized to mimic the stem–loop substrate. Alterations toward the transition state included replacing the substrate adenylate with a hydroxypyrrolidine mimic of the ribocation in an N1′-methylene bridge to 9-deazaadenine placed at the depurination site in tetraloops of varied length (Figures and ). , An abasic, 14mer construct inhibited ricin A-chain with a K d of 480 nM (1N-14, Figure ). Filling the catalytic site with adenine improved binding of IN-14 to 12 nM, demonstrating the benefit of the adenine in combination with the transition state ribocation mimic .…”
Section: Ribosome-inactivating Proteinsmentioning
confidence: 99%
“…Inhibitors were designed and synthesized to mimic the stem–loop substrate. Alterations toward the transition state included replacing the substrate adenylate with a hydroxypyrrolidine mimic of the ribocation in an N1′-methylene bridge to 9-deazaadenine placed at the depurination site in tetraloops of varied length (Figures and ). , An abasic, 14mer construct inhibited ricin A-chain with a K d of 480 nM (1N-14, Figure ). Filling the catalytic site with adenine improved binding of IN-14 to 12 nM, demonstrating the benefit of the adenine in combination with the transition state ribocation mimic .…”
Section: Ribosome-inactivating Proteinsmentioning
confidence: 99%
“…19 These characteristics have been exploited to study changes in RNA structure and binding in ricin toxin protein. 21 When 8VA is base-stacked in DNA its fluorescence is quenched significantly. 18 This kind of behavior is observed in other fluorescent adenine analogues like 2AP [22][23][24][25] and the pteridines 6MAP and DMAP.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work by Kenfack et al showed that 8VA is better stabilized by base stacking than 2-aminopurine (2AP) in dsDNA, and thus they suggest that 8VA is a better probe than 2AP . These characteristics have been exploited to study changes in RNA structure and binding in ricin toxin protein …”
Section: Introductionmentioning
confidence: 99%
“…Early studies identified substrate analogs that target the active site and inhibit RTA with modest inhibitory activity. , However, these compounds had poor solubility, and none of them exhibited potent inhibitory activity against ricin due to the large and highly polar active site . Transition state analogs of the RTA catalytic reaction were powerful inhibitors of the depurination of small stem-loop RNA substrates at low pH but did not protect eukaryotic ribosomes at physiological pH. , High-throughput screening (HTS) of compounds against protein synthesis inhibitory activity or cytotoxicity yielded compounds that target toxin trafficking or cell death pathways but not the toxin itself. …”
mentioning
confidence: 99%